2015
DOI: 10.1302/0301-620x.97b3.34430
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of an unstable slipped capital femoral epiphysis by either intracapsular cuneiform osteotomy or pinningin situ

Abstract: We undertook a retrospective comparative study of all patients with an unstable slipped capital femoral epiphysis presenting to a single centre between 1998 and 2011. There were 45 patients (46 hips; mean age 12.6 years; 9 to 14); 16 hips underwent intracapsular cuneiform osteotomy and 30 underwent pinning in situ, with varying degrees of serendipitous reduction. No patient in the osteotomy group was lost to follow-up, which was undertaken at a mean of 28 months (11 to 48); four patients in the pinning in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Particularly, the Parsch technique 2 of capsulotomy, controlled gentle reduction, and pinning with smooth Kirschner wires for unstable slips has a reported osteonecrosis rate of only 4.7%. However, multiple studies 3,11,35,37,[39][40][41] have also demonstrated an increased rate of osteonecrosis following reduction of an unstable SCFE. These studies have found that, in reduced slips, there is a higher rate of osteonecrosis when higher initial slip angles are present 35 and higher degrees of reduction are achieved 37,41 .…”
Section: Severity Of Slipmentioning
confidence: 99%
“…Particularly, the Parsch technique 2 of capsulotomy, controlled gentle reduction, and pinning with smooth Kirschner wires for unstable slips has a reported osteonecrosis rate of only 4.7%. However, multiple studies 3,11,35,37,[39][40][41] have also demonstrated an increased rate of osteonecrosis following reduction of an unstable SCFE. These studies have found that, in reduced slips, there is a higher rate of osteonecrosis when higher initial slip angles are present 35 and higher degrees of reduction are achieved 37,41 .…”
Section: Severity Of Slipmentioning
confidence: 99%
“… 26 Among unstable hips, a particular difference in practice was that some surgeons enforced a period of ‘bed rest’ prior to surgery, in the belief that there is a time window (between 24 hours and one to two weeks) during which surgery heightens the risk of AVN. 27 , 28 Among those patients with severe deformity, surgeons are generally divided on whether to perform open reduction to normalize the anatomy, albeit risking AVN, or to accept deformity and the symptoms and potential sequelae associated with it. A review by the UK National Institute for Health and Care Excellence noted the safety risk related to AVN, and concluded that the procedure should only be undertaken with special arrangements for governance, consent, audit, and research.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 MDP involves a surgical hip dislocation, creation of a retinacular flap, open reduction of the epiphysis, and internal fixation of the slip to surgically correct the pathoanatomy, avoiding future cartilage damage. 23,25,27 Recent studies have shown that MDP leads to better clinical and radiographic improvement than ISP when treating stable SCFE. 34,38 A 2015 study by Novais et al showed that MDP led to better deformity correction, higher rates of good and excellent Heyman and Herndon clinical outcome, and a lower revision surgery rate compared with ISP for treatment for severe stable SCFE.…”
Section: Discussionmentioning
confidence: 99%